A Multicriteria Analysis to Integrate Stakeholder Perceptions of Ecosystem-Based Flood Adaptations in Coastal Urban Areas - Mar Riera-Spiegelhalder; Luís Campos Rodrigues; Adrián Ferrandis Martínez (Documents d'Anàlisi Geogràfica)
Inland and coastal floods are becoming more frequent and severe, affecting natural and socioeconomic systems. Local adaptation to climate change involves complex decisions which benefit from the integration of opinions from different stakeholders in the design and decision process. This study contributes to the incorporation of stakeholders’ views and preferences in the decision-making process. It uses a living lab (LL) approach to develop a multicriteria analysis (MCA) and is flexible enough to adapt to different geographical contexts and needs. Living lab enables innovative solutions to specific problems to be defined, designed and created through a social-iterative approach. MCA is a suitable decision-making tool, as it allows qualitative parameters to be quantified and evaluation criteria to be weighted. This study presents the results of a MCA applied to the evaluation of Ecosystem-based Adaptation (EbA) to flooding in three coastal city living labs: Vilanova i la Geltrú and Benidorm (Spain) and Oeiras (Portugal). Stabilisation of the riverbed and riverbanks and the planting of riparian vegetation were considered suitable adaptation options to reduce the risk of flooding, particularly in the context of intermittent and perennial rivers, while contributing to significant co-benefits such as biodiversity conservation and improvement, and landscape aesthetic value.